Type of Personality in Adolescents with Cyberbullying - Desi Christin Saragih; Heni Dwi Windarwati; Ayut Merdikawati; Livana PH (Jurnal Ilmu Keperawatan Jiwa, 2020)
Cyberbullying behavior is still quite high among adolescents. This behavior does not have to look face to face because only by using social media and material threats to someone who wants to be a victim. This is closely related to personality types. The research aims to identify personality types in adolescents with cyberbullying. Quantitative research with descriptive methods has been conducted on 126 respondents in one of the high schools in Malang. Data collection using a questionnaire that has been declared valid and reliable. The questionnaire consisted of 35 statements which were categorized into 2 types of personality namely extrovert and introvert. Data were analyzed univariately using a frequency distribution. The results showed that there were 53.2% of respondents had introverted personality types. The results of the study concluded that the majority of adolescents who behave cyberbullying have introverted personality types.